Social and Cultural Barriers to Women's Participation in Pap Smear Screening Programs in Low- and Middle-Income Latin American and Caribbean Countries: An Integrative Review. (November 2018) - Liebermann, Erica J.; VanDevanter, Nancy; Hammer, Marilyn J.; Fu, Mei R.
Purpose: Pap smear screening programs have been ineffective in reducing cervical cancer mortality in most Latin American and Caribbean countries, in part due to low screening rates. The purpose of this review was to analyze recent studies to identify demographic, social, and cultural factors influencing women's participation in Pap screening programs in Latin America and the Caribbean.Design/Method: For this integrative review, cervical cancer screening in Latin America and the Caribbean was searched using PubMed, CINAHL, EMBASE, and PsycINFO databases.Findings/Results: Demographic barriers to screening were socioeconomic status, education, race/ethnicity, and geography. Social barriers included lack of uniformity in screening guidelines, lack of knowledge regarding cervical cancer, and lack of preventive culture. Cultural barriers were fear/embarrassment and gender roles.Conclusions: There are multilevel barriers to Pap smear utilization among women in Latin America and the Caribbean.Implications for Practice: Findings highlight a need for health system engagement, promotion of preventive care, and community-generated educational programs and solutions.